2022
DOI: 10.3390/app12083722
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of a Tunnel Lining Segment Strengthened by In Situ Spraying Mortar

Abstract: After long-term operation, tunnel lining segments encounter various problems. Aiming at these problems, in this paper, we present a method of strengthening tunnel lining segments by in situ spraying mortar. An experimental study of the in situ spraying mortar was carried out to determine the compressive strength, flexural strength and interface properties (splitting tensile strength and shear strength) between concrete and H-70 mortar. The experimental results show that the mechanical properties of H-70 mortar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Wang carried out an experimental study on the durability of engineered cementitious composites (ECC) exposed to sewage environments, simulated by treatments including sulfuric acid exposure and physical erosion [10].The results showed that the residual compressive and tensile strengths of ECC were 30-65% and 300-370% higher than those of the mortar group after 12 corrosion cycles. Wang systematically tested the basic properties of H-70 mortar material [11]. However, with the development of urban drainage pipelines, a large number of inservice pipelines have aged and fallen into disrepair.…”
Section: Introductionmentioning
confidence: 99%
“…Wang carried out an experimental study on the durability of engineered cementitious composites (ECC) exposed to sewage environments, simulated by treatments including sulfuric acid exposure and physical erosion [10].The results showed that the residual compressive and tensile strengths of ECC were 30-65% and 300-370% higher than those of the mortar group after 12 corrosion cycles. Wang systematically tested the basic properties of H-70 mortar material [11]. However, with the development of urban drainage pipelines, a large number of inservice pipelines have aged and fallen into disrepair.…”
Section: Introductionmentioning
confidence: 99%